Stem cell microchimerism and tolerance to non-inherited maternal antigens - Dutta, Partha (Landes Bioscience, 2010)
Exposure to non-inherited maternal antigens (NIMA) in fetal and neonatal life of an F(1) backcross (BDF(1) female × B6 male) mouse can result in lifelong tolerance to allografts expressing the NIMA (H2(d)). We have recently shown that the NIMA-specific regulatory T cells were directly correlated with level of maternal microchimerism (MMc) in adult mice, indicating a causative link between the two, and that both Tregs and multi-lineage MMc were dependent on ingestion of milk from a NIMA(+) mother during nursing. Yet how maternal cells obtained in fetal and neonatal life are maintained in adult life remains unclear. Since stem cells are deficient in MHC class I & II expression, we hypothesized that maternally derived stem cells that replenish MMc remain throughout life without eliciting immunity, but differentiated maternal cells can either be deleted by alloreactive T and B effector cells or persist, inducing NIMA-specific tolerance. Consistent with this hypothesis, we found maternally-derived lineage(neg) c-kit(+) cells in the bone marrow of most of adult offspring by quantitative PCR; however, only 50% had detectable MMc in lineage(+) bone marrow cells. Mesenchymal stem cells (lineage(neg) and plate-adherent cells) propagated from the bone marrow also contained maternally-derived cells, albeit in 10-fold lower frequency compared with MMc in myeloid lineage (CD11b(+) and CD11c(+)) cells. Maternally-derived cardiac stem cells were also detected in lineage(neg) c-kit(+) cells purified from heart tissue of NIMA-exposed mice, indicating a local pool of stem cells sustaining MMc in a non-lymphoid tissue. Cardiac stem cell MMc correlated with the presence of maternally derived cardiomyocytes. Lastly, liver MMc increased after nursing suggesting a seeding of maternal cells into the liver via breast milk. Whether orally-derived liver MMc also included maternal stem cells, was not determined. Maternal stem cells in bone marrow and tissues of NIMA-exposed mice are likely responsible for sustaining MMc in adult mice, but their presence alone does not guarantee multi-lineage MMc and tolerance.